2019
DOI: 10.3390/genes10121022
|View full text |Cite
|
Sign up to set email alerts
|

Periodontitis and Tooth Loss Have Negative Systemic Impact on Circulating Progenitor Cell Levels: A Clinical Study

Abstract: The aim of the present study was to investigate the association and impact of periodontitis and tooth loss on a subtype of endothelial progenitor cell (EPC) levels (CD133+/KDR+). Furthermore, the objective was to determine if the periodontal status influenced CD133+/KDR+ levels. In all, 88 patients with periodontitis and 79 healthy controls (HCs) were enrolled in the study. Enrolled patients were examined and characterized by clinical and blood sample analysis. Spearman’s correlation test was applied in order … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
52
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 61 publications
(55 citation statements)
references
References 51 publications
3
52
0
Order By: Relevance
“…More recently, observational reports have shown an correlation between periodontal disease and cardiovascular disease, including coronary heart disease (CHD), stroke, and endothelial dysfunction 4,5 . Moreover, some studies demonstrated a specifi correlation among periodontal disease and augmented risk of stroke and, in general, CHD [6][7][8] .…”
mentioning
confidence: 99%
“…More recently, observational reports have shown an correlation between periodontal disease and cardiovascular disease, including coronary heart disease (CHD), stroke, and endothelial dysfunction 4,5 . Moreover, some studies demonstrated a specifi correlation among periodontal disease and augmented risk of stroke and, in general, CHD [6][7][8] .…”
mentioning
confidence: 99%
“…The use of skeletal anchorage is getting widespread among orthodontists since it facilitates the management of complex orthodontic biomechanics; as a consequence, skeletal anchorage can be useful in treating borderline cases such as transversal maxillary deficiency in adults. In this respect, miniscrews-assisted rapid maxillary expansion was found to effectively open the mid-palatal suture in adults without the necessity to undergo orthognathic surgery [12,24,[28][29][30][31][32][33][34][35][36][37].…”
Section: Discussionmentioning
confidence: 99%
“…The availability of sufficient supporting bone and the perforation of both cortical laminas (bi-corticalism) are two mandatory parameters for mini-screw stability, especially when orthopedic forces are used, as during skeletal maxillary expansion. In this respect, a quantitative and qualitative evaluation of bone characteristics [30][31][32][33][34][37][38][39][40], as well as the assessment of the most suitable position of the miniscrews in the palate, are critical for the success of maxillary expansion assisted by skeletal anchorage. In this paper, we followed the recent guidelines for digital workflow planning proposed by Cantarella et al [23] for the MSE appliance, however, we utilized the patient CBCT DICOM file that allows discriminating between cortical and cancellous bone.…”
Section: Discussionmentioning
confidence: 99%
“…First, photobiomodulation increases the production of mitochondrial ATP by upregulating the cytochrome c oxidase [12,14,[39][40][41][42][43][44][45] and promotes the cellular viability and the expression of osteocalcin in the tension areas of PDL [12][13][14][15][39][40][41][42][43]. This increased metabolic activity accelerates cellular turnover (osteoclast, osteoblast, and fibroblasts) [44][45][46][47][48][49][50][51][52][53] and the production of cytokines involved in the bone remodeling, mainly the IL-1b [46,[54][55][56][57]. Second, photobiomodulation activates the receptor of nuclear factor kappa B (RANK) and macrophage- Post-treatment radiographic examination such as dental panorex was not required considering the young age of the patient and the short overall treatment time (4 months), thus avoiding useless radiation according to the A.L.A.R.A.…”
Section: Discussionmentioning
confidence: 99%